Development of a Monopoly-Based Educational Game to Enhance Elementary Students’ Understanding of Indonesia’s Geographical Location - Pratiwi, Desiana Retno Rizki; Fathurrahman, Moh. (FKIP Universitas Lampung, 2025)
Development of a Monopoly-Based Educational Game to Enhance Elementary Students’ Understanding of Indonesia’s Geographical Location. Objective: The limited use of learning media by teachers in the classroom learning process affects students' learning outcomes. To enhance these outcomes, appropriate learning media are needed, especially those that align with the characteristics of elementary school students who tend to enjoy play-based activities. One such example is the Monopoly game media, which incorporates captivating images to engage students. This study aims to develop, test the feasibility, and effectiveness of the ekasi monopoly game media to improve student learning outcomes in social and natural science learning outcomes. Methods: This type of research is developmental research (R&D) using the ADDIE development model. The study involved 29 fifth-grade students at SDN Tambakaji 05 Semarang. Data collection techniques included both pretest-posttest and non-test methods, such as observations, interviews, questionnaires, and documentation. Findings: The results indicated that the feasibility of the Ekasi Monopoly Game Media was assessed by media experts at 93.3%, material experts at 97.5%, teachers at 95%, and students at 91.6%, all falling within the